Simple surface modification of poly(methyl methacrylate) microfluidic microplates for enhanced ultrasensitive multiplexed detection of infectious diseases - Sharma T. Sanjay; Sapna Kannan; XiuJun Li (Advanced Sensor and Energy Materials)
Novel strategies for the simultaneous and portable detection of multiple analytes are highly favorable for clinical diagnosis and healthcare. Conventional colorimetric enzyme-linked immunosorbent assay (ELISA) is a widely used laboratory technique for medical diagnostics, quality control, and research applications. However, nonspecific absorption of proteins may lead to a reduction of functional sites, resulting in high background and low sensitivity in ELISA. Herein, we report a simple method of functionalization of poly(methyl methacrylate) (PMMA) with polylysine to be used as the microfluidic microplate substrate for enhanced ELISA, enabling rapid, ultrasensitive, and multiplexed detection of infectious diseases. FTIR and fluorescence microscopy characterization confirmed high amine densities on polylysine-modified PMMA surface, resulting in high detection sensitivity of the colorimetric ELISA on the PMMA microdevice. The ultrasensitive polylysine-modified microplate can immobilize protein within 20 min and results of the assay can be viewed by the naked eye or scanned through a simple desktop scanner for quantitative analysis within 90 min. A sandwich-type immunoassay for the rapid and sensitive detection of immunoglobulin G (IgG), hepatitis B surface antigen (HBsAg), and hepatitis B core antigen (HBcAg) was demonstrated as a proof-of-concept for multiplexed detection. The limits of detection (LOD) of 200.0 pg/mL for IgG, 180.0 pg/mL for HBsAg, and 300.0 pg/mL for HBcAg were achieved, without any specialized equipment like a microplate reader. The surface-modified microchip exhibited about 10-fold higher sensitivity than traditional microplates. This surface-modified microplate has tremendous potential as a point-of-care multiplexed testing platform for many applications ranging from clinical diagnosis to environmental monitoring, particularly in resource-limited settings.